Mangrove Forests in the Andaman and Nicobar Islands - Sahni, K. C. (Indian Forester, 1958)
The Andamans and Nicobars have nearly 1136 Sq. Km. and 35 Sq. Km. (450 and 13.8 square miles) respectively of mangrove forests. They develop in areas covered by brackish water at high tide, such as the mud flats along tidal streams. These forests are of the gregarious type, i.e., they are largely composed of single species or a few allied ones. Some of these species also occur in Malaya and the Philippines where considerable work has been done on their utilization. With a view to the possibility of utilizing them for similar purposes, data have been collected from these countries. The principal products derived are firewoods, charcoal, tan barks, dye barks, and the various products of the Nipa palm including thatching material and alcohol. Tests confirm that they are excellent fuelwoods. Their distribution in the Andamans and Nicobars and their characteristics are described. A key to the genera of mangrove-swamp plants in these islands has been drawn up for rapid identification in the field. The difficulties of extraction and ways to overcome them by improved mechanical means are also described.